Exploring the Future of Human Factors Education: Online Learning, MOOCs, Next Generation Standards, and the Technological Skills We Need to Impart. (September 2016) - Lum, Heather C.; Steelman, Kelly S.; Frederick, Christina M.; Sonnenfeld, Nathan A.; Amato-Henderson, Susan; Smith, Thomas J.
The objective of this panel was to examine how the future of human factors education is changing given the influx of technology, a push for online learning, and adapting to the changing market. The panel will begin by Heather Lum briefly giving an overview and the precipice for this discussion panel. The panelists will provide their views and experiences regarding this topic. Kelly Steelman will discuss the potential for MOOCs and other online formats to create faster and more flexible postgraduate programs. Christina Frederick will discuss her perspectives on the technological skills we should be equipping our human factors graduates with to be successful. Nathan Sonnenfeld will give his unique take on this as a graduate student currently obtaining a human factors education. Susan Amato-Henderson will discuss the Next Generation Science Standards and the ramifications for educators. Lastly, Thomas Smith will focus on the advantages and disadvantages of online learning at the K-12 level. Dr. Lum will foster discussion among the panelists and questions from the general audience. Discussion time: 90 minutes.